2017
DOI: 10.1038/s41598-017-16661-2
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative function of Fmp30, Mdm31, and Mdm32 in Ups1-independent cardiolipin accumulation in the yeast Saccharomyces cerevisiae

Abstract: Cardiolipin (CL) is synthesized from phosphatidic acid (PA) through a series of enzymatic reactions occurring at the mitochondrial inner membrane (MIM). Ups1-Mdm35 mediates PA transfer from the mitochondrial outer membrane (MOM) to the MIM in the yeast Saccharomyces cerevisiae. Deletion of UPS1 leads to a ~80% decrease in the cellular CL level. However, the CL accumulation in ups1∆ cells is enhanced by the depletion of Ups2, which forms a protein complex with Mdm35 and mediates phosphatidylserine (PS) transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Deletion of UPS1 reduced the CL level to ϳ20% of that in WT cells, and the CL level was largely restored on concomitant deletion of UPS2 in ups1⌬ cells (Fig. 3, A and B, lanes 1-3), thus being consistent with previous reports (17,18,26). Depletion of porin proteins in the ups1⌬ ups2⌬ background as well as the UPS1 UPS2 background greatly reduced the CL level ( Fig.…”
Section: Porin Proteins Are Involved In Both the Ups1-dependent And Usupporting
confidence: 91%
See 3 more Smart Citations
“…Deletion of UPS1 reduced the CL level to ϳ20% of that in WT cells, and the CL level was largely restored on concomitant deletion of UPS2 in ups1⌬ cells (Fig. 3, A and B, lanes 1-3), thus being consistent with previous reports (17,18,26). Depletion of porin proteins in the ups1⌬ ups2⌬ background as well as the UPS1 UPS2 background greatly reduced the CL level ( Fig.…”
Section: Porin Proteins Are Involved In Both the Ups1-dependent And Usupporting
confidence: 91%
“…In the present study, we identified a yeast porin protein, Por1 as a protein interacting with the MIM protein Mdm31 (Fig. 1) that is required for Ups1-independent and low mitochondrial PE-enhanced accumulation of CL (26). In addition, we found that Por1 also interacts with the IMS protein Mdm35 (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Our results strongly indicate that when Psd1p is missing or mis-localized, a minimal threshold of PE is not achieved within the IM that is necessary to accumulate normal levels of CL and promote the full activity of the OXPHOS machinery. Although it is presently unclear how the Kennedy Pathway for PE production promotes CL accumulation, it is known that the Ups1p and Ups2p lipid trafficking proteins have an inverse relationship with respect to CL/PE metabolism suggesting that this may be linked to PS/PA trafficking into the IM 3, 54, 55 . Depletion of PS in the psd1 Δ psd2 Δ background restored CL levels to that of psd1 Δ and cho1 Δ which were still comparatively reduced vs WT (Fig 7G).…”
Section: Discussionmentioning
confidence: 99%